PERSEPSI SISWA TENTANG KEPEMIMPINAN GURU DALAM PEMBELAJARAN DI SMA NEGERI 1 ENAM LINGKUNG - Nasyanda Indah Joelia; Novriyanti Achyar; Ermita Ermita; Merika Setiawati (Jurnal Manajemen Pendidikan, 2026)
Objective: his study aims to describe students' perceptions of teacher leadership in learning at SMA Negeri 1 Enam Lingkung. Methods: This research employed a quantitative descriptive approach. The population consisted of 920 students in grades X, XI, and XII, while 287 students were selected using proportional stratified random sampling. Data were collected through a valid and reliable Likert-scale questionnaire and analyzed using descriptive statistics by calculating the mean score. Results: The findings revealed that students' perceptions of teacher leadership in learning were categorized as Good, with an overall mean score of 4.18. Classroom management obtained a mean score of 4.29, motivation and influence on students 4.33, implementation of active and effective learning 4.16, and variation and innovation in teaching methods 3.93, indicating consistently positive perceptions across all indicators. Novelty: This study provides empirical evidence on teacher leadership from students' perspectives at the senior high school level. The findings offer valuable insights for teachers and school administrators to strengthen instructional leadership, improve teaching practices, support effective learning processes, and serve as a reference for future educational research and school policy development in similar educational contexts.